2023
DOI: 10.1038/s41598-023-41798-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, chemical and physical analysis of VDW.1Seal, Fill Root ST, and ADseal root canal sealers

Shehabeldin Saber,
Manar M. Galal,
Amira Galal Ismail
et al.

Abstract: This study aimed to evaluate the thermal, chemical, and physical properties of VDW.1Seal, Fill Root ST, and ADseal sealers. Thermal properties were analyzed using Thermogravimetric analysis (TGA) and Differential thermal analysis (DTA). Attenuated total reflection Fourier Transform Infrared Spectroscopy (ATR-FTIR) analysis was performed as a complementary test to confirm TGA/DTA analysis. The chemical composition of the set sealer material was identified using an X-ray powder diffraction (XRD) system. Other ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The weight stability of the sealer at a high temperature, as assessed using TGA, was similar to that observed in previous studies [27], with higher weight loss observed for CSBS than for AH Plus. These results vary depending on the components and moisture content of the sealers [42]. Therefore, moisture loss after heat application may have contributed to our study results.…”
Section: Discussionmentioning
confidence: 86%
“…The weight stability of the sealer at a high temperature, as assessed using TGA, was similar to that observed in previous studies [27], with higher weight loss observed for CSBS than for AH Plus. These results vary depending on the components and moisture content of the sealers [42]. Therefore, moisture loss after heat application may have contributed to our study results.…”
Section: Discussionmentioning
confidence: 86%
“…It provides information about the degree of crystallinity and the crystalline composition [ 57 ]. The crystallinity of the dental materials provides stability and preservation of the structural integrity against degradation and solubility of the materials by the action of the environment [ 47 , 58 , 59 ]. While, XRF analysis is a rapid, and accurate test to detect chemical elemental compositions [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%